GeoGebra Integration in Elementary Initial Teacher Training: The Case of 3-D Shapes - Putra, Zetra Hainul; Hermita, Neni; Alim, Jesi Alexander; Dahnilsyah, Dahnilsyah; Hidayat, Riyan (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The integration of technology in learning is increasingly popular and inevitable, especially during the Covid-19 pandemic. In mathematics education, Geogebra has been used as a pedagogical tool in learning mathematics from elementary to university. The present study aims to explore first-year prospective elementary teachers’ experience constructing 3-D shapes using GeoGebra. This study uses a case study method with 40 first-year prospective elementary teachers from an elementary initial teacher training from a public university in Riau, Indonesia. The participants worked in small groups and discussed some 3-D shapes through an online platform, and in the end, each participant reflected their attitudes towards the integration of GeoGebra in learning 3-D shapes. The findings show that prospective elementary teachers discussed six types of 3-D shapes; cube, rectangular prism, rectangular pyramid, cylinder, cone, and spheres. They prefer to discuss curved surfaces rather than flat surfaces of 3-D shapes. In addition, prospective elementary teachers have positive attitudes towards integrating GeoGebra in elementary initial teacher training. They believe that GeoGebra supports them to understand better the concepts of volume and surface area of 3-D shapes, facilitate students to understand the properties of a geometry object, and compare the object one made using hand drawing to using GeoGebra. Meanwhile, difficulty in using the tools to construct 3-D shapes in GeoGebra becomes a hinder to understand mathematics concepts and properties. The implication of this study is that there is a potential to integrate GeoGebra in mathematics learning in elementary teacher training.